Persistence of lymphocytic choriomeningitis virus at very low levels in immune mice. - Ciurea, A; Klenerman, P; Hunziker, L; Horvath, E; Odermatt, B; Ochsenbein, A; Hengartner, H; Zinkernagel, R (1999)
Lymphocytic choriomeningitis virus (LCMV), strain WE, is a non-cytopathic RNA virus that is highly adapted to its natural host, the mouse. Acute infection of adult mice leads to generalized virus spread, followed by cytotoxic T lymphocyte-mediated virus clearance below the detection levels of conventional assays within 2-3 weeks. Indirect evidence had suggested that virus or viral antigen might persist in the immune mouse. Here we demonstrate LCMV-WE persistence at low levels after infection with 10(2) or 10(6) plaque-forming units, shown as viral genome, viral antigen, and replicative virus using sensitive in vitro and in vivo assays. The finding that LCMV-WE persists in the face of apparently intact immune responses resembles the situation in some viral (hepatitis B and C, HIV) and bacterial (tuberculosis, leprosy) infections in humans; the results are relevant to the understanding not only of other murine and human persistent viral infections but also of protective immunological memory by "infection immunity."